Aspectos de uma cidade amiga do idoso no núcleo histórico do bairro Vila Nery – São Carlos / SP - Chiusoli, Thaís Carolina (2022)
The rapid growth of the elderly population and the consequent challenges in the cities constitute an alarming scenario. In this sense, the problems involving interpersonal relationships and socio-spatial inequalities that impact the achievement of elderly-friendly places are intensified. In attention to the current situation, the World Health Organization has developed the Global Guide to Age-friendly Cities (GGCAI), which recommend practices based on eight domains that seek to constitute an environment that favors population aging. Thus, the present research aimed to analyze the interactions and integration of elderly residents in the region of the historical nucleus of the Vila Nery neighborhood in the city of São Carlos - SP. This is a cross-sectional, descriptive research, based on the assumptions of the quanti-qualitative method, with an exploratory observational work. By employing the precepts of the rapid estimation technique, five key-informants inserted in services with tradition in the neighborhood were interviewed, considered fundamental parameters for obtaining data, such as: affective experiences, information about characteristics of the services offered, as well as problems and needs for improvements in the place of study, which contribute to the achievement of adequate housing. The analysis of the historical nucleus of Vila Nery, in the light of the eight domains recommended by the GGCAI, supports the understanding that the place presents characteristics of an elderly-friendly place. It was found that the elderly preserves good interpersonal relationships, in addition to a strong sense of belonging to their place of residence. Also, the culture and education of the neighborhood, combined with good communication, favor coexistence and social participation, and the spirit of unity and commitment inherent in the neighborhood contribute to the socio-spatial inclusion of older residents, which emphasizes the importance of the infrastructure and equipment available to the community. The results obtained reveal that aspects such as adequate housing and good social interaction have a direct influence on the quality of life of the elderly, directly impacting on their independence and enjoyment of life in society.